The ‘Urf Perspective of Maanta Bareh Pasaran: Reinforcing the Kinship System through a Local Wisdom in Nagari Balingka - Nofiardi, Nofiardi (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
This study aims to explain the tradition of the Nagari Balingka community, Agam Regency known as maanta bareh pasaran seen from the ‘urf perspective. The study applied a qualitative method with a sociology and descriptive analysis approach. The findings of the study revealed that a niece; kamanakan, if she was married, she was obliged to perform the tradition by visiting the house of her Mamak, bringing the rice (bareh) and the cake (kue gadang) just in time before the Ramadhan as a way to maintain the bond and the relationship of the big family, the matrilineal system in particular. The tradition was in line with the ‘urf admitted in Islam. Referring findings of the study, it could be concluded that the maanta bareh pasaran tradition done by a niece to her mamak helped, in general, to maintain the relationship of every member of the family since there was a bit change of in the role of a Mamak in Minang, and in particular to prolong the matrilineal system. The tradition which was specifically carried out by the people of Nagari Balingka was in line with the ‘Urf perspective.